From Project to Operations: Human Resource Strategies as Key Success Factors for Jakarta-Bandung High-Speed Railway - Zaenudin, Ahmad; Pribadi, Ocky Soelistyo; Handayani, Sri (Journal of International Accounting, Taxation and Information Systems, 2025)
The development of Indonesia’s first high-speed railway between Jakarta and Bandung marks a major transition from infrastructure delivery to full operational readiness, requiring not only physical assets but also competent human resources and an effective technology transfer process. This study examines human resource strategies for the Jakarta–Bandung High-Speed Railway, with a focus on workforce requirement planning, workforce fulfillment, and the localisation of operation and maintenance functions. A qualitative descriptive case study approach was employed, drawing on semi-structured interviews, field observations, and document analysis involving PT Kereta Cepat Indonesia China (PT KCIC), Chinese railway experts, the national railway regulator, and Indonesian railway training institutions. The findings indicate that workforce preparation is implemented through three interrelated strategies. First, a structured workforce requirement planning process integrates service plans, demand forecasting, and asset-based workload analysis, resulting in a projected requirement of 1,483 personnel to support 68 daily train services. Second, workforce fulfillment is conducted in phases through recruitment and secondment schemes, with 513 personnel prepared by mid-2023, leaving 970 positions to be filled. Third, localisation and technology transfer are guided by a roadmap implemented through consortium-based arrangements, staged training programs, and the gradual replacement of 812 Chinese experts in critical operational roles. The study underscores the importance of coherent human resource planning and regulation-aligned localisation strategies in ensuring safe, efficient, and sustainable high-speed rail operations in Indonesia.